Variation of Shear Strength of Clayey Ground During Freezing and Thawing (Izmenie Soprotivleniya Dsvigu Glinistogo Grunta pri ego Promerzanii-Ottaivanii) - Mikhailov,G. D. (1971)
Railroad fills made with clayey ground in the winter frequently deform during spring thawing. The fills settle grossly, the banks cave in, and formation of ballast troughs is observed. One of the causes of such deformations can be lowering of the basic strength index of the soil -- the shear strength -- during freezing and thawing. The Novosibirsk branch of the Research Institute of Transportation Construction has studied the variation in shear strength and cohesion of the soil as a result of freezing and thawing for various soil moistures and densities. Loams taken from pits intended for filling the initial section of the Artyshta-Podobas line were used for the experiments. Samples of the required density and moisture were prepared from the soils in the laboratory. (Author) Draft trans. of Transportnoe Stroitelstvo (USSR) n12 p37-38 Dec 66.